Perceptions of the use of French in product branding among Malaysian female consumers / Alia Athirah Zainudin - Alia Athirah , Zainudin (2024)
This study aimed to investigate the level of awareness, perceptions and understanding among female consumers regarding the use of the French language in beauty product branding. The data was gathered from 102 respondents ranging in age from 18 to 65 years old, who are members of the Facebook group “Kosmetik dan Makeup Malaysia” as well as friends and family. The data was collected through an online survey. The findings showed that 85% of the respondents were aware of the language used in product branding, while only 15% of respondents were unaware of the language used. Additionally, a total of 77.5% of respondents stated that the use of a foreign language such as French in a brand name contributes to the perception of the product as being more expensive and luxurious. The study also revealed that 54.9% of respondents understood the language used in product branding, while 45.1% of respondents did not understand the language used. The study solely focused on female consumers and was limited to beauty products.